An application of the mean-semivariance approach to the portfolio allocation problem: the case of Brazil - Pinheiro, Carlos Alberto Orge (2016)
Made available in DSpace on 2016-10-10T03:52:08Z (GMT). No. of bitstreams: 5 An Application of the mean-semivariance approach to the portfolio allocation problem_The case of Brazil.pdf: 286152 bytes, checksum: 6038000cc527a03d688a2adac4e4f6c8 (MD5) license_url: 52 bytes, checksum: 2f32edb9c19a57e928372a33fd08dba5 (MD5) license_text: 24372 bytes, checksum: 94b0a37ff5ec51de8c55507bff4a7ff9 (MD5) license_rdf: 24623 bytes, checksum: 378d22d8fe50e084ee2f354be78cbe62 (MD5) license.txt: 1887 bytes, checksum: 445d1980f282ec865917de35a4c622f6 (MD5) Previous issue date: 2008-11